2019
DOI: 10.2478/pomr-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Overall Ship Fuel Consumption in Acceleration Manoeuvre Using Hull-Propeller-Engine Interaction Principles and Governor Features

Abstract: The problem of reduction of greenhouse gas emissions in shipping is currently addressed by many research works and related industries. There are many existing and visionary technologies and ideas, which are conceptually defined or practically realised. This goal can be achieved in different ways, and reducing fuel consumption is one of the major methods. In these circumstances, the aim of this study is to analyse the possibility of fuel consumption reduction by using an alternative control strategy for low-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…The mathematical model of the engine is added to the whole model. The engine model used in this study is the same as that presented in [45], and is therefore not repeated here.…”
Section: Model Of Ship Manoeuvresmentioning
confidence: 99%
“…The mathematical model of the engine is added to the whole model. The engine model used in this study is the same as that presented in [45], and is therefore not repeated here.…”
Section: Model Of Ship Manoeuvresmentioning
confidence: 99%
“…Since planing craft are relatively light with a high power-to-weight ratio, they are normally very agile and maneuverable. Zeraatgar and Ghaemi 22 showed that a typical container ship needs about 200 s to change a speed of 9-11.8 m/s. This corresponds to an average surge acceleration of about 0.014 m/s 2 .…”
Section: Analysis Of Accelerating Test Resultsmentioning
confidence: 99%
“…Referring to Fig. 1, the first module has been already presented in [36]. The wave parameters were set in advance, and the variables of the generated wave are measured.…”
Section: Mathematical Modelmentioning
confidence: 99%